Investigating the pedagogy of mathematics : How Do Teachers Develop Their Knowledge? - Fan, Lianghuo (London Imperial College Press, 2014)
This book investigates how mathematics teachers develop their pedagogical knowledge, drawing on two major studies to explore sources such as classroom practice, reflection, collaboration and professional learning activities.
Keywords: Toán học